Clear the fraction by multiplying both sides by 2:
Swap the d and the (n-1)Remove the inner parentheses on the right by distributing:
Remove the remaining parentheses on the right by distributing:
Get 0 on the left by subtracting 2s from both sides:
Swap sides:
Rearrange the terms in descending order Factor n out of the two terms in the middle:
Swap the n and the (2a-d)We use the quadratic formula.
Since there is already a letter "a", we will use capital letters to avoid conflict of notation:
Ax2 + Bx + C = 0 has solution
x = n, A = d, B= (2a-d), C = -2s
3 months ago
Swap the d and the (n-1)Remove the inner parentheses on the right by distributing:
Remove the remaining parentheses on the right by distributing:
Get 0 on the left by subtracting 2s from both sides:
Swap sides:
Rearrange the terms in descending order Factor n out of the two terms in the middle:
Swap the n and the (2a-d)We use the quadratic formula.
Since there is already a letter "a", we will use capital letters to avoid conflict of notation:
Ax2 + Bx + C = 0 has solution
x = n, A = d, B= (2a-d), C = -2s